Submarine geomorphology at the front of the retreating hansbreen tidewater glacier, hornsund fjord, southwest spitsbergen - Cwiakala, Joanna; Moskalik, Mateusz; Forwick, Matthias; Wojtysiak, Kacper; Gizejewski, Jerzy; Szczucinski, Witold (Journal of Maps, 2018)
Source at https://doi.org/10.1080/17445647.2018.1441757 . A 1:10,000 scale bathymetric map as well as 1:20,000 scale backscattering and geomorphological maps of two bays Isbjørnhamna and Hansbukta in the Hornsund fjord (Spitsbergen) present the submarine relief that was primarily formed during and after the retreat of the Hansbreen tidewater glacier. Geomorphological mapping was performed using multibeam bathymetric data and seismoacoustic profiling. The identified landforms include two types of transverse ridges interpreted as terminal and annual moraines, flat areas that are depressions filled with glaciomarine sediments, iceberg-generated pits and ploughmarks, pockmarks and fields of megaripples. Most of the identified landforms are genetically related to the retreat of Hansbreen since the termination of the Little Ice Age at the beginning of the twentieth century. Although Hansbreen has been speculated to be a surge-type glacier, no evidence of surging was identified in the submarine landform assemblage, which is in accordance with the absence of historically documented surges for that period.